2001
DOI: 10.1248/bpb.24.242
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Activities of 1.ALPHA.,25-Dihydroxyvitamin D3 and Its Synthetic Analog 1.ALPHA.,25-Dihydroxy-16-ene-vitamin D3 in Normal Human Osteoblastic Cells and Human Osteosarcoma SaOS-2 Cells Are Modulated by 17-.BETA. Estradiol and Dependent on Stage of Differentiation.

Abstract: Recent evidence suggests that the bone anabolic effects of the active hormone 1a, 25(OH) 2 D 3 ] are mediated via a direct action on cells of the osteoblastic lineage.1) In a number of studies, however, the doses required for anabolic effects were associated with toxicity due to hypercalcaemia and hypercalciuria.2,3) Previous studies have reported the syntheses of a number of analogs of 1a,25(OH) 2 D 3 , and these analogs can mimic the effects of the parent compound without causing hypercalcaemia.4) As such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…In this study, 1α,25(OH) 2 D 3 at higher concentrations significantly increased ALP activity in 143B cells but not in SaOS‐2 cells. The stimulation of ALP activity by 1α,25(OH) 2 D 3 at higher concentration in 143B cells supports the study hypothesis that 1α,25(OH) 2 D 3 can promote OS cell differentiation, and conforms with research in other human OS cells 15, 33, 36, 58–61. The ability of 1α,25(OH) 2 D 3 to promote ALP activity at 100 nM concentration and not at higher concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, 1α,25(OH) 2 D 3 at higher concentrations significantly increased ALP activity in 143B cells but not in SaOS‐2 cells. The stimulation of ALP activity by 1α,25(OH) 2 D 3 at higher concentration in 143B cells supports the study hypothesis that 1α,25(OH) 2 D 3 can promote OS cell differentiation, and conforms with research in other human OS cells 15, 33, 36, 58–61. The ability of 1α,25(OH) 2 D 3 to promote ALP activity at 100 nM concentration and not at higher concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the massive 1a, 25-Dihydroxyvitamin D 3 -depentent increase of ALPP and OC expression observed in OS2 and OS5, confirmed their capacity to respond to vitamin D compounds differentiating stimuli as observed for other OS commercial cell lines (Hansen et al, 2001;Li et al, 2008;Thompson et al, 2012). Moreover, their greater responsiveness to 1a, 25-Dihydroxyvitamin D 3 compared to HOb, was in agreement with an early stage differentiation that is typical of OS (Rao et al, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…This is congruent with the chondroblastic origin of OS1 or it might be due to OS1 lack of nuclear vitamin D receptor (VDR), even if no correlation between OS subtype and expression of VDR could be established (Gallagher et al, 2012). Moreover it could be attributed both to a more differentiated stage of the original tumor (Rao et al, 2001) or it could be due to the loss of function of vitamin D 3 signaling pathway including its cognate receptor (Matsugaki et al, 2010). OS2 and OS5 exhibited an osteoblastic phenotype as confirmed by strong positive ALPP and OC expression ( Fig.…”
Section: Discussionmentioning
confidence: 84%
“…After chromatography the oil residue was treated with 1 M tetrabutylammonium fluoride in tetrahydrofuran (3 mL). The reaction mixture was stirred at room temperature for 20 h. Workup and chromatography on column (25 mL, protected from light) using 1:1 hexane/ethyl acetate as mobile phase gave 24 mg (44%) of 13as colorless oil; H NMR (CDCl 3 …”
Section: α-Fluoro-25-hydroxy-20r-(4-hydroxy-4-methyl-pentyl)-2122r-mentioning
confidence: 99%
“…2 These changes are designed to retard the degradation of the ligand within the target cells, and to induce an active conformational change of the VDR. Previous studies of calcitriol derivatives demonstrated that the introduction of the C-16 double-bond in the D-ring affects the conformation of the side-chain, improves the biological stability by arresting the metabolic degradation at the 24-keto stage, 3 generally enhances differentiation and anti-proliferative activity, 4 and reduces the hypercalcemic potential. 5 Structural modifications of the side-chain itself also interfere with the C-24 hydroxylation-initiated cascade of degradation and modify biological activities.…”
Section: Introductionmentioning
confidence: 99%